ANALISIS PENALARAN MATEMATIS SISWA PADA MATERI FUNGSI EKSPONEN - Marlan, Marlan; Ratumanan, Tanwey Gerson; Palinussa, Anderson Leonardo (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2023)
This research was motivated by the difficulties of SMA Negeri 5 Maluku Tengah students in understanding exponential function material. One of the abilities that must be possessed to understand mathematics is mathematical reasoning. This research uses qualitative descriptive research methods. The subjects in this research were 3 students selected from 34 students based on their odd semester final exam scores for the 2021/2022 academic year in the high, medium and low categories. The instruments used were test question and interview guidelines. The test instrument consist of 4 essay questions which are prepared based on mathematical reasoning indicators and have been validated. The research result show that overall student mathematics is in the medium category with a percentage 50%. All three subjects can fulfill all rhe specified mathematical reasoning indicators. The subject’s ability to carry out mathematical reasoning is determined by the subject’s initial knowledge and subject’s ability to use his knowledge in developing appropriate solution strategies